2012
DOI: 10.1088/0953-8984/24/35/355601
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between crystal field splitting and Kondo effect in CeNi9Ge4−xSix

Abstract: The pseudo-ternary solid solution CeNi(9)Ge(4-x)Si(x) (0 ≤ x ≤ 4) has been investigated by means of x-ray diffraction, magnetic susceptibility, specific heat, electrical resistivity, thermopower and inelastic neutron scattering studies. The isoelectronic substitution of germanium by silicon atoms causes a dramatic change of the relative strength of competing Kondo, RKKY and crystal field (CF) energy scales. The strongest effect is the continuous elevation of the Kondo temperature T(K) from approximately 3.5 K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Also, it is observed that magnetic hysteresis is absent in both of these compounds (not shown). properties in low temperature region [32,34]. For La_0.4 compound, it is noted that resistivity rises around T I , followed by a maximum around T II (upper inset of Fig.2 (b)).…”
Section: Results and Discussion -mentioning
confidence: 90%
See 1 more Smart Citation
“…Also, it is observed that magnetic hysteresis is absent in both of these compounds (not shown). properties in low temperature region [32,34]. For La_0.4 compound, it is noted that resistivity rises around T I , followed by a maximum around T II (upper inset of Fig.2 (b)).…”
Section: Results and Discussion -mentioning
confidence: 90%
“…For La_0.4 compound, a peak is observed around T I followed by a weak anomaly around T II (shown by an arrow). The curve is featureless for La_0.76 compound because the transition temperature is shifted below 1.8 K. For both compounds, it is noted that with decreasing temperature C increases and attains broad maxima around 155 K. Such feature possibly arises due to the presence of incoherent Kondo scattering along with the CEF effect[32]. Upper inset ofFig.…”
mentioning
confidence: 92%
“…The full moment degeneracy is preserved by the high-temperature Kondo scattering, which serves to effectively quench the local crystal-field splitting. Such an effect is observed in the case of CeNi 9 Si 4 , which has a full 6-fold degenerate ground state when chemical tuning sets T K = 70 K, comparable to the crystal-field splitting 46 . The large low-temperature J in URu 2 Si 2 gives rise to a strong magnetic excitation spectrum and, of course, a large configurational degeneracy.…”
Section: Relation To Electronic Structurementioning
confidence: 87%
“…We now introduce the deviations from the strong field limit as ( ) ( / ) ,1 5 r r r n n n g g A T u r = →∞ + ≤ ≤ (7) and rewrite equations (5) in terms of ( ) r n u :…”
Section: Model and Thermodynamic Equationsmentioning
confidence: 99%
“…Kondo temperatures given in eq. (6) and(7) of ref. 11 are reproduced numerically by the present calculations.…”
mentioning
confidence: 99%